Assessment of quality of life in post burn survivors: A cross-sectional single-center first validation study from Pakistan. Issue 1 (January 2018) - Shahid, Faiza; Ismail, Mohammad; Khan, Salman
Highlights: The HRQoL of post burn survivors were assessed by EQ-5D-3L questionnaire. Majority of participants were children in aged group 3–10 years. The post burn period, depth and extent of burn injury has significantly negative impact on several health dimensions of EQ-5D-3L. Rehabilitation programs should be implemented to improve the functional outcomes. Abstract: Background: Burns are major health problem and fourth frequent cause of trauma, following falls, road incidences and interpersonal violence worldwide. The present study aimed to assess socio-demographic risk factors and quality of life (EQ-5D-3L) in post burn patients presenting to the outpatient department. Methods: The present study was designed cross sectional study completed in a period of six months (March 2016 to August 2016). The overall subjects were selected from the outpatient department. The EQ-5D-3L score EQ-5D index and VAS questionnaire were completed by interviewing face to face individuals. Finally, the data was analyzed by SPSS IBM 20. Results: The present study revealed that demographic characteristics (age and gender), socioeconomic variables (low literacy level, low economic status, occupation, urban residence and nuclear family structure) are prognostic risk factors associated with burn related injuries. The mean age of the sample was 17.08 years. The most frequent cause of burns was scald followed by flame. Children (46%) of aged 3–10 years were predominant sustained scald and flame burns. Female proportion was high (56%) and were significantly sustained scald and flame burn, whereas, male was observed by electric (84.2%) and contact burns (78.3%). The upper limbs anatomical part was most commonly affected (11–20%) TBSA burned in 36.4% patients and 71.6% sustained partial thickness and mixed deep thickness. Majority of the incidence take place at home (88.4%). Among co-morbidities, Diabetes mellitus was observed the most common (4.4%). Post burn complications such as infection, surgeries, hypertrophic scars and contractures were reported in 16%, 28.4%, 14.8% and 7.2% respectively. The majority of participants was assessed in first year of post burn period (87.2%) and reported moderate to severe problem in each health dimension of EQ-5D instrument. The depth and extent %TBSA burn and post burn period have negative impact on health dimensions EQ-5D scores. Conclusion: Our findings revealed that quality of life was compromised in majority of post burn patients. Several demographic characteristics such as young age and female gender, low socioeconomic status and clinical parameters related burns were important risk factors in assessment of quality of life in burn sustained patients.